Analisis kebutuhan pengembangan panduan praktikum pada matakuliah gelombang berbasis pendekatan STEM - Lora, Haditya A; Lestari, Ladia (Kumparan Fisika, 2025)
The purpose of this paper is to analyze the need for the development of wave practicum guidelines in the Physics Education study program at the University of Bengkulu. This study uses a direct survey method, interview techniques, and the distribution of online form-based questionnaires to students, practicum assistants, laboratory assistants, and lecturers. Based on the data obtained and analyzed, the results show that the Physics Education study program has not carried out practicums in the laboratory directly for a long time after the post-covid era, and the existing practicum guidelines have not been updated since the last curriculum change, while laboratory equipment has been updated, and students find it difficult to receive material due to the lack of guidance for direct wave practicums both in groups and independently, this is because students only do wave practicums through Phet Simulation, resulting in a lack of direct experience with the laboratory, and also assembling tools. Based on the results of the analysis, it was concluded that the need for the development of wave practicum guidelines based on the STEM approach to meet the practical needs of students in higher education.